ANALISIS KEMAMPUAN SISWA SEKOLAH DASAR DALAM MENYELESAIKAN SOAL-SOAL MATEMATIKA MODEL THE TRENDS FOR INTERNATIONAL MATHEMATICS AND SCINECE STUDY (TIMSS) DI PEKANBARU - Gustimal Witri; Zetra Hainul Putra; Nori Gustina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2014)
The aim to do this research is to investigate fifth grade students of Primary School to solveTIMSS problem in Pekanbaru. Lack of information about fifth grade students' abilities inIndonesia to solve TIMSS problems is the reason to do this research. The method used in thisresearch was the mixed methods approach. The data were collected from 134 fifth gradestudents from Primary School Teacher Education (PGSD) partnership Primary School inPekanbaru. Twenty TIMSS problems were tested to those students, and the result showed thatthe fifth grade students of Primary School in Pekanbaru still achieved low category. They gotdifficulties in solving TIMSS problems especially on data display and reasoning in cognitiveaspect. Meanwhile, there was not significantly different between boys and girls in solvingTIMSS problems. Key words: TIMSS problems, Mixed Methods Approach, Data Display, Reasoning, andCognitive Aspect.